2011
DOI: 10.1073/pnas.1012500108
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal amplification of leucine-rich repeat kinase-2 (LRRK2) is required for oncogenic MET signaling in papillary renal and thyroid carcinomas

Abstract: The receptor tyrosine kinase MET is frequently amplified in human tumors, resulting in high cell surface densities and constitutive activation even in the absence of growth factor stimulation by its endogenous ligand, hepatocyte growth factor (HGF). We sought to identify mechanisms of signaling crosstalk that promote MET activation by searching for kinases that are coordinately dysregulated with wild-type MET in human tumors. Our bioinformatic analysis identified leucine-rich repeat kinase-2 (LRRK2), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 36 publications
0
69
0
Order By: Relevance
“…Recent cohort study revealed the relationship between parkinson’s disease and cancer72. Also in molecular-level studies, the PARK2 and LRRK2 genes well known in parkinson’s disease were revealed that those genes were related with cell cycle pathways7374.…”
Section: Resultsmentioning
confidence: 99%
“…Recent cohort study revealed the relationship between parkinson’s disease and cancer72. Also in molecular-level studies, the PARK2 and LRRK2 genes well known in parkinson’s disease were revealed that those genes were related with cell cycle pathways7374.…”
Section: Resultsmentioning
confidence: 99%
“…Looyenga and colleagues (20) identified LRRK2 as a mechanism of signaling cross-talk that promotes MET activation, tumor cell growth, and survival in papillary renal and thyroid carcinomas. We confirmed that LRRK2 is amplified and upregulated across pRCC and highly correlates with MET expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been previously demonstrated that MET-triggered pathway implicates several upstream regulators and coreceptors that are physically associated with MET either at the cell surface or intracytoplasmic domain that might consequently induce MET transactivation (15). For instance, leucine-rich repeat kinase 2 (LRRK2) has recently been reported as a required kinase for MET oncogenic signaling in pRCC (20). We therefore investigated the potential impact of both ligand and coactivators required for MET activation in pRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Many functional roles for LRRK2 have been suggested, including vesicular trafficking and endocytosis [11,12], protein synthesis [13], immune response regulation [14], inflammation [15] and cytoskeleton homoeostasis [16]. Finally, LRRK2 has been associated with TNFα (tumour necrosis factor α) [17], Met [18], interferon γ [19] and MAPK (mitogen-activated protein kinase) [20] signalling pathways. However, there is still no consensus on LRRK2 function, and its physiological role(s) remain to be elucidated.…”
Section: Lrrk2: An Enigma Of Function(s)mentioning
confidence: 97%